Penerapan Model Pembelajaran Berbasis Masalah Berbantuan GeoGebra untuk Meningkatkan Kemampuan Komunikasi Matematis Siswa SMP Negeri 1 Kolang - Winny Thesa Sianturi; Pardomuan N.J.M. Sinambela (Departement of Mathematics Education, 2024)
The research aims to improve the mathematical communication skills of SMP Negeri 1 Kolang students by applying a problem based learning model assisted by GeoGebra. The research subjects were 30 grade VIII students of SMP Negeri 1 Kolang. The type of research used was classroom action research which was carried out in 2 actions. The two actions were carried out in 4 meetings in learning and 2 evaluations. The results of the study show that mathematical communication skills can improve after using the GeoGebra assisted problem based learning model. The increase was obtained through an average students score of 42.7 with 7% classical mastery to 67.5 with 50% classical mastery in action I and to 83.05 with 87% classical mastery in action II. An increase was also obtained through teacher observation of 2.56 in action I to 3.30 in action II. So it was concluded that the application of the problem based learning model assisted by GeoGebra can improve the mathematical communication skills of students of SMP Negeri 1 Kolang.